Establishing prostate cancer patient derived xenografts: Lessons learned from older studies. Issue 6 (5th January 2015) - Russell, Pamela J.; Russell, Peter; Rudduck, Christina; Tse, Brian W‐C; Williams, Elizabeth D.; Raghavan, Derek
Abstract: Background: Understanding the progression of prostate cancer to androgen‐independence/castrate resistance and development of preclinical testing models are important for developing new prostate cancer therapies. This report describes studies performed 30 years ago, which demonstrate utility and shortfalls of xenografting to preclinical modeling. Methods: We subcutaneously implanted male nude mice with small prostate cancer fragments from transurethral resection of the prostate (TURP) from 29 patients. Successful xenografts were passaged into new host mice. They were characterized using histology, immunohistochemistry for marker expression, flow cytometry for ploidy status, and in some cases by electron microscopy and response to testosterone. Two xenografts were karyotyped by G‐banding. Results: Tissues from 3/29 donors (10%) gave rise to xenografts that were successfully serially passaged in vivo. Two, (UCRU‐PR‐1, which subsequently was replaced by a mouse fibrosarcoma, and UCRU‐PR‐2, which combined epithelial and neuroendocrine features) have been described. UCRU‐PR‐4 line was a poorly differentiated prostatic adenocarcinoma derived from a patient who had undergone estrogen therapy and bilateral castration after his cancer relapsed. Histologically, this comprised diffusely infiltrating small acinar cell carcinoma with more solid aggregates of poorly differentiated adenocarcinoma. The xenografted line showed histology consistent with a poorly differentiated adenocarcinoma and stained positively for prostatic acid phosphatase (PAcP), epithelial membrane antigen (EMA) and the cytokeratin cocktail, CAM5.2, with weak staining for prostate specific antigen (PSA). The line failed to grow in female nude mice. Castration of three male nude mice after xenograft establishment resulted in cessation of growth in one, growth regression in another and transient growth in another, suggesting that some cells had retained androgen sensitivity. The karyotype (from passage 1) was 43–46, XY, dic(1;12)(p11;p11), der(3)t(3:?5)(q13;q13), ‐5, inv(7)(p15q35) x2, +add(7)(p13), add(8)(p22), add(11)(p14), add(13)(p11), add(20)(p12), ‐22, +r4[cp8]. Conclusions: Xenografts provide a clinically relevant model of prostate cancer, although establishing serially transplantable prostate cancer patient derived xenografts is challenging and requires rigorous characterization and high quality starting material. Xenografting from advanced prostate cancer is more likely to succeed, as xenografting from well differentiated, localized disease has not been achieved in our experience. Strong translational correlations can be demonstrated between the clinical disease state and the xenograft model. Prostate 75: 628–636, 2015 . © The Authors. The Prostate published by Wiley Periodicals, Inc.